Intercorporeality comes from the beginning: the co-constitution of infant self-awareness - Ximena González-Grandón; Gerónimo Rangel (Cogent Arts & Humanities)
Traditionally, the study of self-awareness has often been disconnected from the body and space. An interesting exception is neonatal imitation theories, which emphasize proprioceptive mechanisms, body schema, and the role of copying others, in developing the self. However, grounded in representational cognitive frameworks, these theories often portray infants and caregivers as passive participants, overlooking that early interactions are dynamic, spatially oriented, and reciprocal in nature. Adopting an enactive and ecological perspective, this article argues that even the most minimal forms of embodied self-awareness are inherently relational and emerge through early embodied interactions with caregivers. In the first months of life, proprioceptive experiences of interbodily interactions –reciprocal, active body-to-body exchanges– play a crucial role in shaping an infant’s embodied self-awareness. By emphasizing the interdependence of these perceptual exchanges, we reframe early development as a relational and co-constituted process, inseparable from the social and affective dynamics of caregiving.